MEDIATION AND THE PLURILINGUAL / PLURICULTURAL DIMENSION IN LANGUAGE EDUCATION (ItalianoLinguadue, 2023)
This article explains the integrated, complex, situated view of languages and language education that is gradually replacing the linear, ‘Cartesian’ view of languages as inert objects to be dissected, which has long dominated language education. It discusses the way mediation can act as a prism. Exactly as a prism decomposes white light into the spectrum of its constituting colours, mediation can help one grasp and handle the complexity of languages, itself augmented by the increasingly diverse nature of our classrooms. In discussing the plurilingual nature of mediation, the article introduces descriptors from the 2020 CEFR Companion Volume and explains the concepts of languaging and plurilanguaging (Piccardo, 2017, 2018), showing how mediation and the languaging involved in it can contribute to a new vision of an action-oriented, plurilingual language education. Finally, the article explains and illustrates the concept of action-oriented scenarios, giving a brief account of two implementation projects, one mainly in Canada and one in Lombardy, reporting the very positive effects on student motivation and engagement.  La mediazione e la dimensione plurilingue/pluriculturale nell’educazione linguisticaQuesto contributo presenta la visione integrata, complessa e situata della lingua e del suo insegnamento che sta gradualmente sostituendo la visione lineare, ‘cartesiana’ delle lingue come oggetti inerti da sezionare, che per molto tempo ha dominato l’educazione linguistica. L’articolo propone una discussione sulla maniera in cui la mediazione agisca in modo simile ad un prisma ottico. Esattamente come un prisma scinde la luce bianca nei colori che la costituiscono, la mediazione può favorire la comprensione e la gestione della complessità delle lingue, essa stessa sempre più crescente per la natura via via più diversificata delle classi attuali. Nel discutere la natura plurilingue della mediazione l’articolo introduce i descrittori del Volume complementare del Quadro comune europeo di riferimento (QCER) e spiega i concetti di languaging e plurilanguaging (Piccardo, 2017, 2018), mostrando come la mediazione e il processo di languaging che essa comporta contribuisca ad una visione dell’insegnamento delle lingue orientata all’azione e plurilingue. Infine, l’articolo spiega ed illustra il concetto di scenario azionale, fornendo un breve resoconto di due progetti di utilizzo di tali scenari, uno in Canada e l’altro in Lombardia, riportandone gli effetti molto positivi sulla motivazione e sull’investimento personale degli allievi.